2018
DOI: 10.1016/j.cell.2018.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Two to Tango: Dialog between Immunity and Stem Cells in Health and Disease

Abstract: Summary Stem cells regenerate tissues in homeostasis and under stress. By taking cues from their microenvironment or “niche”, they smoothly transition between these states. Immune cells have surfaced as prominent members of stem cell niches across the body. Here, we draw parallels between different stem cell niches to explore the context-specific interactions that stem cells have with tissue resident and recruited immune cells. We also highlight stem cells’ innate ability to sense and respond to stress, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(161 citation statements)
references
References 93 publications
(152 reference statements)
6
153
0
2
Order By: Relevance
“…It is therefore not surprising that quiescence (as well as Gpha2 expression) is lost ex vivo, whereas culture conditions are sub-optimal and lacking essential components of the niche. The co-localization of T cells with qLSC strongly implies that these cells may secret cytokines to control LSC quiescence, in line with previous studies where immune cells were identified as niche cells for epithelial SCs 88 . In the clinics, corticosteroids such as dexamethasone are being widely used to prevent uncontrolled corneal inflammation and neo-vascularisation, as these agents are considered as highly effective drugs for nonspecific suppression of inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…It is therefore not surprising that quiescence (as well as Gpha2 expression) is lost ex vivo, whereas culture conditions are sub-optimal and lacking essential components of the niche. The co-localization of T cells with qLSC strongly implies that these cells may secret cytokines to control LSC quiescence, in line with previous studies where immune cells were identified as niche cells for epithelial SCs 88 . In the clinics, corticosteroids such as dexamethasone are being widely used to prevent uncontrolled corneal inflammation and neo-vascularisation, as these agents are considered as highly effective drugs for nonspecific suppression of inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, phagocytosis of newborn cells has also been recently shown to play a role in sculpting sex differences in the developing amygdala (VanRyzin et al, 2019). While previous work has suggested a largely detrimental effect of microglia on hippocampal neurogenesis (Valero et al, 2016), our data are in agreement with recent evidences supporting the essential role of macrophages and other immune cells in remodeling stem cells niches (Naik et al, 2018).…”
Section: Phagocytosis Reprograms Microgliasupporting
confidence: 92%
“…Thus, through their ability to sense and respond to niche signals, stem cells can adjust to and survive stressful situations. Remarkably, stem cells form an enduring epigenetic memory from such encounters, which equips them with the ability to mobilize more rapidly during subsequent assaults 6,95 .…”
Section: Trained Immunity In Stromal and Epidermal Stem Cellsmentioning
confidence: 99%